Conceptualization of e-professionalism among physics student teachers - Nurfarahin Nasri; Nik Mohd Rahimi; Harwati Hashim; Nurfaradilla Mohamad Nasri (International Journal of Evaluation and Research in Education (IJERE), 2023)
The ever-growing digital world has driven the rise of various social media platforms, creating unique challenges for school teachers. Incidents involving teachers’ unprofessional online behavior may potentially damage careers and the reputation of the teaching profession. Accordingly, this constructivist grounded theory research interviewed 38 physics student teachers (PSTs) to explore how they perceive e-professionalism and its impact on their future teaching careers. Data involving PSTs’ current social media practices, professional identity reflection and awareness of social media content were analyzed manually using hybrid thematic analysis. Findings reveal the use of social media mainly focuses on Facebook, Instagram, WhatsApp, Telegram and TikTok where distinction between social online identity and professional identity were commonly blurred. The PSTs’ notions of classroom selfies and political expressions on social media were likely attributed to a lack of related regulations, policies or guidelines. Moreover, a finding of major concern is the PSTs’ hesitancy to act upon inappropriate online behaviors. Their lack of professional awareness and knowledge of e-professionalism can be traced back to their training period where less emphasis was given to developing their competencies in this area. This research has crucial practical implications for designing a relevant teacher education curriculum to effectively address e-professionalism.